2006
DOI: 10.1073/pnas.0603082103
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of mda-5 in type I IFN responses to polyriboinosinic:polyribocytidylic acid and encephalomyocarditis picornavirus

Abstract: The innate immune system recognizes viral dsRNA through two distinct pathways; the Toll-like receptor 3 (TLR3) pathway detects dsRNA phagocytosed in endosomes; the helicases retinoic acidinduced protein I (RIG-I) and melanoma differentiation-associated gene-5 (mda-5) detect cytoplasmic dsRNA generated during viral replication. Both RIG-I and mda-5 can bind polyriboinosinic:polyribocytidylic acid (polyI:C), the synthetic analog of viral dsRNA, and mediate type I IFN responses to polyI:C and multiple RNA viruses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
918
5
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,018 publications
(979 citation statements)
references
References 46 publications
37
918
5
3
Order By: Relevance
“…Although polyI:C was first described as a TLR3 ligand [17], it has been recently shown that polyI:C is also recognized by the Mda5 helicase, a member of the RIG-1 like receptor family that also triggers type I IFN production [5,32,33]. Recent data suggest that TLR3 and Mda5 may act synergistically to induce type I IFN [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although polyI:C was first described as a TLR3 ligand [17], it has been recently shown that polyI:C is also recognized by the Mda5 helicase, a member of the RIG-1 like receptor family that also triggers type I IFN production [5,32,33]. Recent data suggest that TLR3 and Mda5 may act synergistically to induce type I IFN [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…PolyI:C induces anti-viral immunity [17,29], reduces tumor progression via a type I IFN-mediated NK cell activation [30], and reduces hepatitis through enhancing NK-cell activities [31]. In accordance with these in vivo properties, our data suggest that the stimulatory properties of polyI:C could be, at least partly, related to the induction of type I IFN production by NK cells.Although polyI:C was first described as a TLR3 ligand [17], it has been recently shown that polyI:C is also recognized by the Mda5 helicase, a member of the RIG-1 like receptor family that also triggers type I IFN production [5,32,33]. Recent data suggest that TLR3 and Mda5 may act synergistically to induce type I IFN [34][35][36].…”
mentioning
confidence: 99%
“…65 This hypothesis is supported by the observation that Mda-5 appears to predominate over RIG-1 in type I IFN responses to polyIC, as these responses are abrogated in Mda-5 À/À dendritic cells and macrophages. 69 This can be due either to the fact that responses to polyIC require the concerted activation of RIG-1 and Mda-5, or to the difference between the affinities or specificities of RIG-1 and Mda-5 for polyIC. The observation that Mda-5 is selectively required for cytokine responses to encephalomyocarditis picornavirus but not to other viruses supports the hypothesis that Mda-5 and RIG-1 have different specificities for dsRNA.…”
Section: Role Of Rip1 In the Innateosome Complexmentioning
confidence: 99%
“…Retinoic acid-inducible gene-I (RIG-I) and melanoma differentiation-associated gene 5 (MDA5) are cytoplasmic RNA helicases [1][2][3], which signal the presence of viral RNA through the adaptor, IFN-b promoter stimulator-1 (IPS-1) (also known as mitochondrial antiviral signaling protein/caspase recruitment domain (CARD) adaptor inducing IFN-b (Cardif)/virus-induced signaling adaptor) to produce IFN-b [4][5][6][7]. IPS-1 localizes on the outer membrane of the mitochondria via its C-terminus [6].…”
Section: Introductionmentioning
confidence: 99%